UU PERKAWINAN DAN KHI DALAM PERSPEKTIF FILSAFAT HUKUM: BERISTRI LEBIH DARI SEORANG - Aminah, Siti; Fathoni, Achmad (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
The issue of the law of a husband having more than one wife (read: polygamy) has always been an interesting discussion. Although the pros and cons surrounding the law of polygamy have been going on for a long time, until now on every opportunity the discussion of polygamy has always presented quite a fierce debate. Especially since the emergence of issues regarding gender and human rights, not a few contemporary islamic jurists and feminists have tried to review the law on polygamy. There are at least three groups of views on the law of polygamy: 1) those who absolutely allow polygamy, 2) those who allow it under certain conditions and conditions. 3) those who absolutely forbid. In this paper, we will not discuss the pros and cons of polygamy. because the law of polygamy in Indonesia is allowed even with certain conditions. The author will focus on explaining how legal philosophy views Law no. 1 of 1974 and the Compilation of Islamic Law which regulates the regulation of having more than one wife. Then analyzes these rules from the perspective of legal philosophy.